2005
DOI: 10.1590/s0066-782x2005001500008
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão arterial sistêmica no setor de emergência: o uso de medicamentos sintomáticos como alternativa de tratamento

Abstract: Blood pressure (BP) was reduced below levels for discharge criteria for a (non-significant) higher rate of patients treated with symptomatic drug, who were turned into asymptomatic after the observation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
1
1
Order By: Relevance
“…A study carried out in 2000 at the Emergency Department of Hospital de Base in the city of São José do Rio Preto, found 83.5% of emergencies and 86.6% of hypertensive emergencies in caucasian patients, showing that most of the individuals with hypertension were caucasian, as observed in the present study 28 . Differently from the present study, the results demonstrated at the Hospital Universitário Oswaldo Cruz in the city of Recife, state of Pernambuco, at the Cardiology Emergency Unit, where patients with hypertensive crises and symptoms associated with elevated BP were treated from May 2001 to October 2002, showed that 75% of the patients treated during this period were classified as non-caucasians 29 .…”
Section: Discussioncontrasting
confidence: 99%
“…A study carried out in 2000 at the Emergency Department of Hospital de Base in the city of São José do Rio Preto, found 83.5% of emergencies and 86.6% of hypertensive emergencies in caucasian patients, showing that most of the individuals with hypertension were caucasian, as observed in the present study 28 . Differently from the present study, the results demonstrated at the Hospital Universitário Oswaldo Cruz in the city of Recife, state of Pernambuco, at the Cardiology Emergency Unit, where patients with hypertensive crises and symptoms associated with elevated BP were treated from May 2001 to October 2002, showed that 75% of the patients treated during this period were classified as non-caucasians 29 .…”
Section: Discussioncontrasting
confidence: 99%
“…Headaches, as the primary complaint, were independently associated with hypertensive pseudocrisis. In this regard, Nobre and associates 16 found that 88% of the patients who complained of a headache were wrongly diagnosed with hypertensive crisis, and Lima and associates 17 obtained better results using analgesics in comparison to anti-hypertensive medications for the clinical picture of "hypertension and headache" in the emergency room. Other publications have been trying to disassociate the headache as a secondary effect of the elevation in BP 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the deaths were a result of neurological complications, which agrees with the findings of studies on hypertensive emergency complications 8 . On the other hand, data in literature [2][3][4] and practical results from studies on the use of pharmaceuticals to treat elevated BP symptoms in the emergency room 17 , indicate these medications as the therapy of choice for hypertensive pseudocrisis situations. Therefore, patients with this clinical condition should be assessed with utmost caution before anti-hypertensive therapy is administered; the initial symptoms (emotion, pain, discomfort, epistaxis, etc) should be treated and controlled, since they should be considered as the cause and not the consequence of the elevated blood pressure levels, particularly when there is no risk of acute target organ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Ela também af eta pessoas de origem chinesa, japonesa e outras origens asiáticas ou do Pacíf ico (como coreanos, tailandeses, polinésios , micronésios, f ilipinos e maoris). As consequências da hipertensão arterial são piores em negros e descendentes de asiáticos (LIMA SG, et al, 2005).…”
unclassified